Hair Dye Poisoning: An Important Aetiological Factor in Acute Renal Failure in Gezira, Sudan - Osman, Wail N; Elhaj, Abu Sufyan H. A.; Elmustafa, Osman M; Taha, Sami Mahgoub; M. Ahmed, Mohammed El Imam (Gezira Journal of Health Sciences, 2012)
Introduction : Hair dye containing paraphenylene diamine (PPD) is widely used in Sudan for cosmetic reasons and the compound is known to be allergic and highly toxic.  Objectives : To study the prevalence and clinical features of hair dye poisoning (HDP) among patients with acute renal failure (ARF) and the outcome of management in Gezira, Central Sudan.  Patients and methods : This is a retrospective hospital based study, conducted in Gezira Hospital for Renal Diseases and Surgery (GHRDS) on 171 (105 females and 66 males)  patients with ARF, during the period from June 2006 to May 2007. Results : Total number of patients presenting with Hair dye poisoning (HDP) was 55. Hair dye poisoning (HDP) was the most common cause of ARF in 32.16% (n=55) patients followed by severe malaria in 24.56% (n=42), severe sepsis\septic shock in 16.96% (n=29), dehydration and volume depletion in 13.45% (n=23), urinary tract infections in 10.53% (n=18) and obstructive uropathy in 2.34% (n=4) of the cases. Patients with HDP were two males (3.64%) and 53 females (96.36%), and the most commonly affected age group was 15–24 years in 70.91% of the cases. Most cases of HDP were due to suicidal attempts in 76.36% (n=42) and were encountered in the majority of cases by females (97.62%). Other features of HDP were angioneurotic oedema in 25.5%, dark discoloration of urine in 100%, abdominal pain in 32.7%, flaccid paraplegia in 18.2%, cranial nerves palsies 14.5% and convulsions in 5.5% of cases.  Outcome of treatment of ARF due to HDP showed complete recovery in 81.8% and progression to chronic kidney disease (CKD) in 18.2% of the patients. Mortality rate was zero. Conclusion and recommendation : HDP due to PPD intoxication is the main causative factor of ARF in GHRDS. Both public and official awareness is needed about the serious complications of this substance. Interdisciplinary collaboration is necessary for management, proper treatment and help to minimize complications and improve outcome.